OPPORTUNITIES FOR STRENGTHENING GENDER EQUALITY THROUGH TOURISM (International Educators Conference, 2025)
Tourism is one of the fastest-growing sectors in the international economy and provides income and social change. (UNSWTO,2022) As a sector with a strong labour-related focus, tourism offers many job opportunities especially for women, but gender inequality persists in terms of income, leadership and access to decision-making opportunities. This study measured the success of tourism to increase gender equality, using Uzbekistan's past experience as well as current practices from around the world. The paper outlines the impact of women in tourism, the barriers that exist and the options available to remove those barriers. Overall it was concluded that tourism has the opportunity to become a strong catalyst for gender equality and social equity, if it is developed and managed in a sustainable and inclusive fashion.